Magnetic bead purification of enveloped alphavirus and flavivirus - Bianca Galasso (Elsevier, 2021)
Virus production is an essential part of virology. The quality of virus preparation, in terms of purification and yield, can affect the outcome of experiments. Purified virus is critical for assays, as contamination from cell culture supernatants may affect results. Purified virus is also needed for vaccine preparations. The traditional process of gradient purification of virus is time consuming, with multiple steps spanning over days, and produces significant amounts of biohazard waste. Developing a more efficient alternative that provides a purified virus product is highly desirable. In this study, we performed magnetic bead purification of Zika virus (ZIKV) and Mayaro virus (MAYV) with the Mag4C LV kit from OZ Biosciences. Currently, this kit is only indicated for use with lentiviruses and retroviruses. We found that we were able to successfully concentrate and purify both ZIKV and MAYV using the kit. Therefore, we concluded that the Mag4C LV kit provides a quick and simple alternative to traditional virus purification methods. • Our protocol is customized by using an alphavirus (MAYV) and flavivirus (ZIKV). This method has not been previously used for these viruses.